2007
DOI: 10.1093/aje/kwm181
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Pollution and Preterm Birth in the Environment and Pregnancy Outcomes Study at the University of California, Los Angeles

Abstract: The authors conducted a case-control survey nested within a birth cohort and collected detailed risk factor information to assess the extent to which residual confounding and exposure misclassification may impact air pollution effect estimates. Using a survey of 2,543 of 6,374 women sampled from a cohort of 58,316 eligible births in 2003 in Los Angeles County, California, the authors estimated with logistic regression and two-phase models the effects of pregnancy period-specific air pollution exposure on the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
261
6
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 344 publications
(287 citation statements)
references
References 46 publications
16
261
6
4
Order By: Relevance
“…Over the past few years an increasing amount of evidence derived from studies focused particularly on male fertility and pregnancy outcome showed the negative effects of environmental contaminants derived from traffic emissions, including ozone (O3), CO, SOx, NOx, benzene, formaldehyde, PAHs, and suspended PM present in urban air on human reproductive health [9][10][11][12][13][14]. In contrast, few studies were able to demonstrate an association between air pollution and fertility impairment in women, probably due to the multiplicity of factors involved in female reproductive function [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years an increasing amount of evidence derived from studies focused particularly on male fertility and pregnancy outcome showed the negative effects of environmental contaminants derived from traffic emissions, including ozone (O3), CO, SOx, NOx, benzene, formaldehyde, PAHs, and suspended PM present in urban air on human reproductive health [9][10][11][12][13][14]. In contrast, few studies were able to demonstrate an association between air pollution and fertility impairment in women, probably due to the multiplicity of factors involved in female reproductive function [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The association of NO 2 exposure and PTB was explored in 10 studies (Bobak, 2000;Gehring et al, 2011;Jalaludin et al, 2007;Leem et al, 2006;Liu et al, 2003;Llop et al 2010;Maroziene and Grazuleviciene, 2002;Ritz et al,2000Ritz et al, , 2007Ritz et al, , 2011 (Table 2). Bobak (2000) (first and third trimester), Maroziene and Grazuleviciene(2002) (first trimester), Leem et al (2006), Bobak (2000) (first and third trimester), Llop et al (2010) (second and third trimester and entire pregnancy) reported an increased risk of PTB; however, others reported no association.…”
Section: Air Pollution and Preterm Deliverymentioning
confidence: 99%
“…Bobak (2000) (first and third trimester), Maroziene and Grazuleviciene(2002) (first trimester), Leem et al (2006), Bobak (2000) (first and third trimester), Llop et al (2010) (second and third trimester and entire pregnancy) reported an increased risk of PTB; however, others reported no association. The association between CO exposure and preterm birth was explored in 6 studies (Ritz et al, 2000;Huynh et al, 2006;Leem et al, 2006;Liu et al, 2003;Wilhelm and Ritz, 2005;Ritz et al, 2007). Liu et al (2003) (last month of the pregnancy), Wilhelm and Ritz (2005) (first trimester), leem et al (2006) (first and third trimester) and Ritz et al (2007) (first trimester) reported a higher risk of PTB with higher concentration of CO. 4 of 6 studies reported a higher risk of PTB with CO exposure around 1ppm.…”
Section: Air Pollution and Preterm Deliverymentioning
confidence: 99%
See 2 more Smart Citations